Faktor-Faktor yang Memperngaruhi Kinerja Akademik Mahasiswa : Analisis Structural Equation Model - Fransiskus Janu Hamu; Donatus Wea; Nerita Setiyaningtiyas (Universitas Pendidikan Mandalika, 2023)
This study aims to determine and explore the factors influencing student academic performance at St. Yakobus Merauke. This study used a quantitative approach with a probability sampling method to obtain information and data from respondents. Primary data was collected from 149 students, and data analysis techniques used structural equation model (SEM) analysis with AMOS 26.00 software. The results of this study indicated that the factors of social responsibility, student-teacher relationships, and student satisfaction had a significant effect on student academic performance. In addition, some elements must be considered, namely the ability of soft skills. This ability is related to the ability to cooperate with other people, interact with lecturers, build better communication relationships, and create a conducive and positive classroom climate which plays an important role in making the teaching and learning process more effective and efficient.